Endodontic infections increase leukocyte and lymphocyte levels in the blood - Samuel, Renata Oliveira [UNESP]; Gomes-Filho, João Eduardo [UNESP]; Azuma, Mariane Maffei [UNESP]; Sumida, Dóris Hissako [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Ciarlini, Paulo César [UNESP]; Narciso, Luis Gustavo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Springer Nature, 2018)
Objectives: The aim of this study was to determine whether the presence of single or multiple apical periodontitis (AP) alters blood cell counts and cytokine production. Material and methods: Thirty rats were divided into three groups: a control group comprising rats without AP, a group called 1AP comprising rats with AP in one tooth, and a group called 4AP comprising rats with AP in four teeth. Endodontic infection was induced by pulp exposure of the first right maxillary molar in the 1AP group or by exposing the first and second right maxillary and mandibular molars in the 4AP group. A blood count and cytokine levels were obtained 30 days after infection by collecting blood by cardiac puncture. The maxillae were dissected and stained with hematoxylin and eosin to evaluate the inflammatory infiltrate. The data were tabulated and subjected to statistical analysis (P < 0.05). Results: Histological analysis showed a predominance of mononuclear inflammatory cells. In blood, significant increase of leukocytes, lymphocytes, and tumor necrosis factor alpha (TNF-α) in 4AP compared with the control and 1AP groups (P < 0.05) was observed. In addition, significant decrease of interleukin-4 (IL-4) in 1AP and 4AP groups compared with the control was observed (P < 0.05). Conclusions: In the rat model, the presence of multiple AP can affect health by increasing lymphocyte and TNF-α levels in the blood. Clinical relevance: The presence of endodontic infections can interfere with the blood profile, altering systemic health.
Keywords: Apical periodontitis; Blood count; Leukocytes; Lymphocytes